George Yeo [Singapore, Minister of Foreign Affairs] - Yeo, George (Institutional Knowledge at Singapore Management University, 2017)
George Yeo, former Minister of Foreign Affairs who became a business leader, speaks to DNA about his philosophical Taoist worldview, the impact of the rise of China, and the challenges facing ASEAN at its 50th year. He talks on how the soft power of ASEAN's policy of non-interference has yield some successes.